OPTION SEBAGAI SALAH SATU ALTERNATIF DALAM MENGHADAPI RESIKO PERUBAHAN KURS - Farah Margaretha (Universitas Trisakti, 2002)
The discussion about option is always to the point of how to decrease the risk in the decision making about finance. Especially that related with the foreign exchange. This paper is try to analyze about what is the meaning of the option, option pricing, what is the role of the option and how to decide the price and option value and also how to decrease the risk by option.